2003
DOI: 10.1097/01.wnr.0000071767.24455.10
|View full text |Cite
|
Sign up to set email alerts
|

Selectively reduced regional cortical volumes in post-traumatic stress disorder

Abstract: Different subterritories of anterior cingulate cortex (ACC) and adjacent ventromedial frontal cortex have been shown to serve distinct functions. This scheme has influenced contemporary pathophysiologic models of psychiatric disorders. Prevailing neurocircuitry models of post-traumatic stress disorder (PTSD) implicate dysfunction within pregenual ACC and subcallosal cortex (SC), as well as amygdala and hippocampus. In the current study, cortical parcellation of magnetic resonance imaging data was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(79 citation statements)
references
References 22 publications
4
72
0
3
Order By: Relevance
“…The PVTp projection to mPFC targets IL in a highly preferential manner (Moga et al, 1995), warranting consideration of this region in the adaptive adjustments of the axis to chronic stress. From a pathological perspective, neuroimaging studies reveal functional impairment and shrinkage of mPFC in posttraumatic stress disorder (PTSD) (Rauch et al, 2003;Shin et al, 2005) that find a parallel in reports of dendritic atrophy and synapse loss after chronic emotional stress in rodents (Cook and Wellman, 2004;Radley et al, 2004Radley et al, , 2006. PTSD is associated with HPA axis dysregulation that may be variable in nature (for review, see Newport and Nemeroff, 2000;Yehuda, 2001) and consistent increases in cardiovascular reactivity Shalev et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The PVTp projection to mPFC targets IL in a highly preferential manner (Moga et al, 1995), warranting consideration of this region in the adaptive adjustments of the axis to chronic stress. From a pathological perspective, neuroimaging studies reveal functional impairment and shrinkage of mPFC in posttraumatic stress disorder (PTSD) (Rauch et al, 2003;Shin et al, 2005) that find a parallel in reports of dendritic atrophy and synapse loss after chronic emotional stress in rodents (Cook and Wellman, 2004;Radley et al, 2004Radley et al, , 2006. PTSD is associated with HPA axis dysregulation that may be variable in nature (for review, see Newport and Nemeroff, 2000;Yehuda, 2001) and consistent increases in cardiovascular reactivity Shalev et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI studies have observed reductions in gray matter volume in participants with PTSD, in both rostral (Rauch et al 2003;Woodward et al, 2006;Kasai et al, 2008;Herringa et al 2012) and caudal (Woodward et al, 2006;Chen et al, 2012;Chao et al, 2013) subdivisions of the ACC. In many cases, these volume reductions correlated with PTSD symptom severity.…”
Section: Anterior Cingulate Cortex and Ptsdmentioning
confidence: 99%
“…Thus, an important line of inquiry is whether individuals with PTSD show changes in ERN amplitude. This is particularly salient in light of the structural and functional alterations in MFC observed in this disorder (Hamner et al, 1999;Shin et al, 2001;Rauch et al, 2003;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…More specifically, vmPFC engagement during extinction learning predicts extinction success and is associated with “top‐down” modulation of amygdala‐driven fear expression (Do‐Monte, Manzano‐Nieves, Quiñones‐Laracuente, Ramos‐Medina, & Quirk, 2015; LebrĂłn, Milad, & Quirk, 2004; Milad et al., 2005, 2007; Phelps, Delgado, Nearing, & LeDoux, 2004; Quirk, Likhtik, Pelletier, & ParĂ©, 2003; Rosenkranz, Moore, & Grace, 2003). Results from studies with PTSD patients revealed deficits in extinction recall (Milad et al., 2008), reduced vmPFC volume, and activation during fear extinction compared to controls (Bremner et al., 2005; Milad et al., 2009; Rauch et al., 2003; Rougemont‐BĂŒcking et al., 2011; Shin, Rauch, & Pitman, 2006). Therefore, facilitating endogenous vmPFC activity using brain stimulation techniques, in the context of extinction learning, may be one method to improve fear extinction and retention (i.e., recall of safety memories; Milad & Quirk, 2002; Milad, Vidal‐Gonzalez, & Quirk, 2004) in those suffering from PTSD.…”
Section: Introductionmentioning
confidence: 99%